GENETIC IMPROVEMENT IN SMALL MILLETS: A REVIEW - Nascimento, Giovanna de Souza Sá; dos Santos, Isla Mikaele Alves; de França, José Geraldo Eugênio; Santos, José Peroba de Oliveira; de Amorim, Agda Taynná; Oliveira, Ana Lyvia Ferreira De Paula; de Sá, Carlos Gabriel Quidute; Alves, Cleber Pereira (Editora Impacto Científico, 2025)
Small millets have emerged as strategic crops for agricultural systems in semi-arid and low-productivity regions due to their high adaptive efficiency, short growth cycle, and significant nutritional value. The broad genetic diversity present among different millet groups offers important opportunities for the development of more stable, productive, and stress-tolerant cultivars. However, the predominance of self-pollination and reduced floral structure hinder natural crossing, making the use of specific emasculation and hybridization techniques essential to enhance genetic recombination. In recent years, significant advances in genomics—such as the use of SNP markers, marker-assisted selection, and genome-wide analysis approaches—have accelerated the identification of alleles associated with stress tolerance, yield potential, and nutritional quality. International programs coordinated in India, Africa, and by institutions such as ICRISAT have expanded the available genetic base, while also promoting resilient cultivars adapted to different production systems. At the same time, the growing socioeconomic appreciation of these cereals reinforces their emerging role in food security. This review integrates biological, genetic, and applied aspects, presenting the main advances and perspectives for strengthening small millet breeding. DOI: https://doi.org/10.56238/edimpacto2025.085-007